The dynamic trio: The relationship between passion, perseverance and job satisfaction - Mitja Gorenak; Nataša Uršič; Igor Rajner (Tourism)
This work aims to enhance the understanding of the dynamic relationship between passion, perseverance and job satisfaction among tour guides, recognizing the interconnected nature of these elements and their impact on tourism experience. A quantitative survey was conducted among a representative sample of tour guides using two pre-existing validated questionnaires, allowing the results to be generalized to the entire population. The findings provide a comprehensive understanding of the complex dynamics within the tourism industry, particularly regarding tour guides. While passion, perseverance and job satisfaction are interrelated, their correlations exhibit specific characteristics; passion does not directly dictate job satisfaction, whereas perseverance is a significant contributor. This research emphasizes the importance of commitment, combining both passion and perseverance, and offers insights that can inform managerial decisions and human resources (HR) policies concerning tour guides in tourist agencies.